Impurity-enhanced solid-state amorphization: the Ni–Si thin film reaction altered by nitrogen. (5th February 2019) - van Stiphout, K; Geenen, F A; Santos, N M; Miranda, S M C; Joly, V; Demeulemeester, J; Detavernier, C; Kremer, F; Pereira, L M C; Temst, K; Vantomme, A
Abstract: Solid-state amorphization, the growth of an amorphous phase during annealing, has been studied in a wide variety of thin film structures. Whereas research on the remarkable growth of such a metastable phase has mostly focused on strictly binary systems, far less is known about the influence of impurities on such reactions. In this paper, the influence of nitrogen, introduced via ion implantation, is studied on the solid-state amorphization reaction of thin (35 nm) Ni films with Si, using in situ x-ray diffraction (XRD), ex situ Rutherford backscattering spectrometry, XTEM, and synchrotron XRD. It is shown that due to small amounts of nitrogen (<2 at.%), an amorphous Ni–Si phase grows almost an order of magnitude thicker during annealing than for unimplanted samples. Nitrogen hinders the nucleation of the first crystalline phases, leading to a new reaction path: the formation of the metal-rich crystalline silicides is suppressed in favour of an amorphous Ni–Si alloy; during a brief temperature window between 330 and 350 °C, the entire film is converted to an amorphous phase. The first crystalline structure to grow is the orthorhombic NiSi phase. We demonstrate that this impurity-enchanced solid-state amorphization reaction occurs only under specific implantation conditions. In particular, the initial distribution of nitrogen upon implantation is crucial: sufficient nitrogen impurities must be present at the interface throughout the reaction. Introducing implantation damage without nitrogen impurities (e.g. by implanting a noble gas) does not cause the enhanced solid-state amorphization reaction. Moreover, we show that the stabilizing effect of nitrogen on amorphous Ni–Si films (with a composition ranging from 40% to 50% Si) is not restricted to thin film reactions, but is a general feature of the Ni–Si system.